Downregulation of P-cadherin expression in hepatocellular carcinoma induces tumorigenicity - Bauer, Richard; Valletta, Daniela; Bauer, Karin; Thasler, Wolfgang E.; Hartmann, Arndt; Mueller, Martina; Reichert, Torsten E.; Hellerbrand, Claus (International Journal of Clinical and Experimental Pathology, 2014)
P-cadherin is a major contributor to cell-cell adhesion in epithelial tissues, playing pivotal roles in important morphogenetic and differentiation processes and in maintaining tissue integrity and homeostasis. Alterations of P-cadherin expression have been observed during the progression of several carcinomas where it appears to act as tumor suppressive or oncogenic in a context-dependent manner. Here, we found a significant downregulation of P-cadherin in hepatocellular carcinoma (HCC) cell lines and tissues compared to primary human hepatocytes and non-malignant liver tissues. Combined immunohistochemical analysis of a tissue microarray containing matched pairs of HCC tissue and corresponding non-tumorous liver tissue of 69 patients confirmed reduced P-cadherin expression in more than half of the cases. In 35 human HCC tissues, the P-cadherin immunosignal was completely lost which correlated with tumor staging and proliferation. Also in vitro, P-cadherin suppression in HCC cells via siRNA induced proliferation compared to cells transfected with control-siRNA. In summary, downregulation of P-cadherin expression appears to induce tumorigenicity in HCC. Therefore, P-cadherin expression may serve as a prognostic marker and therapeutic target of this highly aggressive tumor.
EVALuna2:6674